2017
DOI: 10.1055/s-0037-1604201
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser for Endoscopic Treatment of Benign Tracheal Stenosis

Abstract: Introduction  Laryngotracheal stenosis is a difficult problem with varied etiology and various treatment options. The holmium laser represents another tool for the treatment of benign tracheal stenosis. Objectives  To determine the utility of holmium laser treatment for benign tracheal stenosis with regards to safety and efficacy. Methods  This was a retrospective case study examining patients with benign tracheal stenosis from 1998–2016 who underwent holmium laser treatment. Determining the safety of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, holmium laser possesses several properties over CO 2 laser 21,22 : (i) it can be transmitted by fiber‐optic delivery system to get reliable access to lobar and segment bronchi and target the lesion of tracheobronchial tree more precisely; (ii) it has a unique feature of minimal penetration depth to approximately 0.4 mm, which minimizes collateral damage to the surrounding tissues; (iii) its maximal effective distance is only 5 mm, limiting unwanted firing of the laser into normal tissue; and (iv) it cuts thick scar tissue and bone without overheating, and shows good hemostasis. Verret et al 23 demonstrated no intraoperative or postoperative complications were found in the utility of holmium laser treatment for benign tracheal stenosis. Likely, we successfully ablated granuloma without any complication related to holmium laser use.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, holmium laser possesses several properties over CO 2 laser 21,22 : (i) it can be transmitted by fiber‐optic delivery system to get reliable access to lobar and segment bronchi and target the lesion of tracheobronchial tree more precisely; (ii) it has a unique feature of minimal penetration depth to approximately 0.4 mm, which minimizes collateral damage to the surrounding tissues; (iii) its maximal effective distance is only 5 mm, limiting unwanted firing of the laser into normal tissue; and (iv) it cuts thick scar tissue and bone without overheating, and shows good hemostasis. Verret et al 23 demonstrated no intraoperative or postoperative complications were found in the utility of holmium laser treatment for benign tracheal stenosis. Likely, we successfully ablated granuloma without any complication related to holmium laser use.…”
Section: Discussionmentioning
confidence: 97%
“…This is, to our knowledge, the first report about a patient cohort treated with FED-LD with a PHL. In the upper aerodigestive tract PHL has been used for treatment of benign tracheal stenosis with extremely low rate of adverse events [ 13 ]. In our study, the safety of FED-LD has been demonstrated with a low rate of intraoperative adverse events of 4% (2 cases) which were both managed endoscopically during the same intervention without any need for further interventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of the PHL in comparison to the CO 2 laser is the short wavelength and thereby short penetration of the tissue resulting in a clean and sharp cut [ 13 ]. Therefore, a complete dissection of the common wall of the diverticulum without increasing the risk of transmural defects is possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ease of use with a fiber also enables this laser to be used endoscopically with flexible scopes. Hence, in case 5, holmium laser was preferred [ 20 ].…”
Section: Discussionmentioning
confidence: 99%